2023
DOI: 10.1021/acscatal.3c04085
|View full text |Cite
|
Sign up to set email alerts
|

A Gatekeeper Residue Controls Aromatic Acceptor Specificity of the PHB-Type UbiA Prenyltransferases

Erlan Yang,
Yongpeng Yao,
Yihan Liu
et al.

Abstract: UbiA prenyltransferases (PTs) play an important role in prenylation of aromatic compounds with diverse bioactivities. The deep and comprehensive understanding of their substrate selectivity and catalytic mechanism will facilitate the expansion of the robust biocatalytic tools for prenylation of aromatic compounds. Herein, we identified an atypical PHB-type UbiA PT (ClaS) from the basidiomycete Clitocybe clavipes. Unexpectedly, ClaS transferred geranyl pyrophosphate (GPP) to hydroquinone (HYQ) instead of p-hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…ClaS was previously characterized as an atypical PHB-type UbiA PT capable of transferring geranyl pyrophosphate (GPP) to hydroquinone to form 2 (Figure 2d). 29 We then mined a gene encoding an FAD-dependent monooxygenase (named CcDC) from the C. clavipes genome and confirmed its decarboxylation ability toward PHB to produce hydroquinone (Figures S2 and S3). These results suggested that the cla BGC is responsible for clavilactone biosynthesis and facilitated identification of the macrocyclase responsible for formation of the benzo-fused macrocycle.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…ClaS was previously characterized as an atypical PHB-type UbiA PT capable of transferring geranyl pyrophosphate (GPP) to hydroquinone to form 2 (Figure 2d). 29 We then mined a gene encoding an FAD-dependent monooxygenase (named CcDC) from the C. clavipes genome and confirmed its decarboxylation ability toward PHB to produce hydroquinone (Figures S2 and S3). These results suggested that the cla BGC is responsible for clavilactone biosynthesis and facilitated identification of the macrocyclase responsible for formation of the benzo-fused macrocycle.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…PP505398), which mainly encodes a UbiA prenyltransferase (PT) ClaS, a laccase, and seven cytochrome P450s. ClaS was previously characterized as an atypical PHB-type UbiA PT capable of transferring geranyl pyrophosphate (GPP) to hydroquinone to form 2 (Figure d) . We then mined a gene encoding an FAD-dependent monooxygenase (named CcDC) from the C. clavipes genome and confirmed its decarboxylation ability toward PHB to produce hydroquinone (Figures S2 and S3).…”
Section: Results and Discussionmentioning
confidence: 99%